The Effectiveness of Coal-Based Organic Fertilizer and Cow Manure on Yield Quality of Several Tomato Varieties (Lycopersicum esculentum L.) - Made Sri Yuliartini; I Gusti Made Arjana; Ida Bagus Komang Mahardika (Agriwar Journal, 2021)
Tomato is an important vegetable crop and has been widely cultivated as a garden plant or commercially. The purpose of this study was to measure the effectiveness of organic fertilizer based on coal and cow dung based on several tomato varieties. This study used a factorial randomized design with two factors, namely the type of fertilizer consisting of "Saputra" coal fertilizer (BB), "Bio Alam Asri" manure (BA) and without organic fertilizer (B0); and the other factor is the tomato variety factor (V), namely Servo F1 (VS), Gustavi F1(VG), and Fortuna 23 (VF). Based on the results of the study, it was found that the treatment of BB and BA, in general, had a significant effect on vegetative growth and generative yields including fruit quality in the three tomato varieties tested. The highest number and fresh weight of tomatoes per plant were obtained in the treatment of BB, namely 44.00 fruits and 3.00 kg, higher than BA fertilizer, namely 39.11 fruit and 2.62 kg, and B0 namely 34.00 pieces and 2.20 kg. The highest number and fresh weight of tomatoes per plant were obtained in VS varieties, namely, 42.33 fruits and 2.74 kg, followed by VG varieties at 40.11 fruits and 2.71 kg and the lowest was VF at 34.67 fruit and 2.38 kg. The highest vitamin C content of fresh fruit was obtained in the BB treatment, which was an average of 36.75 mg/100g, higher than the treatment with BA fertilizer and B0, which were 32.81 mg/100g and 31.07mg/100g.